The times of emergence of the adults tomato leafminer Tuta absoluta (Meyrick) in spring and the number of heat units needed for this as well as its relationship to the damage caused by the insects - AL-Shammary, Ahmed J. (Journal of Kerbala for Agricultural Sciences, 2022)
The objective of this study was aimed to determine the emergence date of tomato leafminer Tuta absoluta (Meyrick) in Essaouira / Wasit governorate fields during the spring seasons of 2015, 2016 and 2017. The results indicated that the adults began to emerge during the first ten days of March in all years of this study. Accumulate of 116.24 degree-days (based on 9.64 C° as a lower threshold developmental) was necessary for the first emergence. the results also showed that the accumulation of 118.84 , 127.20 , 140.06 and 150.42 degree-days were necessary for emergence of 10, 50 , 75 and 100 % respectively of the total over wintering population in 2015 . While the accumulation of 118.68 , 130.04 , 141.90 , 151.90 and 162.70 degree-days were necessary for emergence of 10, 25 , 50 , 90 and 100 % respectively in 2016 , whereas the accumulation of 111.02 , 124.06 , 135.42 , 146.28 and 167.00 degree-days were necessary for emergence of 10, 50 , 75 , 90 and 100 % respectively in 2017, Most adults ( 100%) were able to emerge after 23.67 days during March , the The evolution of sex ratio ( females : males ) for adults of the first generation was nearly 1.33:1.